AKK-derived outer membrane vesicles alleviate indomethacin-induced mucin secretion reduction in LS174T cells by inhibiting endoplasmic reticulum stress - Zhang, Lijun; Ma, Shuang; Liang, Huixi; Chen, Xin; Zhao, Jingwen (Frontiers in Molecular Biosciences, 2024)
IntroductionAKK-derived outer membrane vesicles (AKK-OMVs) have shown potential in modulating intestinal mucosal immunity by increasing the number of intestinal goblet cells. However, it remains unclear whether AKK-OMVs can directly regulate MUC2 secretion in goblet cells exposed to indomethacin in vitro and the underlying mechanisms involved.MethodsThe abnormal mucin secretion model in LS174T cells was established using indomethacin, with treatment including Akkermansia muciniphila (AKK) supernatant, AKK-OMVs, and extracellular vesicle removal supernatant. The effects of these treatment on MUC2 expression were observed. Transcriptomic sequencing analysis was used to explore the underlying regulatory mechanisms, which were further validated through qRT-PCR and western blotting.ResultsThe treatment with AKK supernatant and AKK-OMVs alleviated the indomethacin-induced reduction in MUC2 secretion in goblet cells. Mechanistically, transcriptomic analysis showed that the gene expression associated with endoplasmic reticulum (ER) stress were upregulated after indomethacin treatment in LS174T cells. This suggests that AKK-OMVs, as the active component in the supernatant, improved MUC2 expression by inhibiting ER stress.ConclusionAKK-OMVs can directly stimulate goblet cells to promote MUC2 secretion, providing potential for further in vivo studies to confirm their protective effects against indomethacin-induced intestinal injury.